2001
DOI: 10.1111/j.1151-2916.2001.tb01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Ink‐Jet Printing of Wax‐Based Alumina Suspensions

Abstract: Suspensions of fine alumina powder in a paraffin wax have been successfully formulated with viscosity values sufficiently low to allow ink-jet printing using a commercial printer. A commercial-grade paraffin wax, with stearylamine and a polyester, were used as the dispersant system. Suspensions with powder loadings up to 40 vol% were passed through the ink-jet printer head. Unfired ceramic bodies with a feature size of <100 m have been successfully fabricated with waxes that had a powder loading of 30 vol%. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
165
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(171 citation statements)
references
References 20 publications
5
165
0
1
Order By: Relevance
“…Hence a different dispersant system based on a commercial polyester was studied. Previous work on alumina had identified the Hypermer series of dispersants as being particularly effective with alumina [5,6] and these were explored for use with PZT. It is well known that a combination of long chain and short chain surfactant molecules can be particularly effective in dispersing ceramics particles [71.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence a different dispersant system based on a commercial polyester was studied. Previous work on alumina had identified the Hypermer series of dispersants as being particularly effective with alumina [5,6] and these were explored for use with PZT. It is well known that a combination of long chain and short chain surfactant molecules can be particularly effective in dispersing ceramics particles [71.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that a combination of long chain and short chain surfactant molecules can be particularly effective in dispersing ceramics particles [71. Earlier work had shown that Hypermer LPI can be used with octadecanoic acid (stearic acid) and octadecylamine to produce suspensions of alumina in wax with very low viscosity [5,61 Suspensions of PZT in wax were prepared containing 1 wt% Hypermer LP1 and 0.5 wt% octadecylamine and a range of PZT powder concentrations. These were ball milled for 6 hours at 120 °C to ensure adequate dispersion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts have been made to prepare ceramic inks in the form of zirconia suspension and suspension of alumina powder in paraffin wax with viscosity values sufficiently low to allow inkjet printing using a commercially available printer [3][4][5] . In these studies, viscosity, surface tension, and dispersion achieved in the inks, drying rate, and green strength of the deposit were considered.…”
Section: Preparation Of Ceramic Inkmentioning
confidence: 99%
“…Drop impact onto a solid surface is a key process in many applications involving electronic fabrication 1 , spray coating 2 , and additive manufacturing using inkjet printing 3,4 , where a precise control of drop spreading and splashing is desired. However, direct observation of drop impact is technically challenging for two reasons.…”
Section: Introductionmentioning
confidence: 99%